Submaximal elastic resistance band tests to estimate upper and lower extremity maximal muscle strength - Haraldsson, Bjarki T. (2021)
Muscle strength assessment is fundamental to track the progress of performance and prescribe correct exercise intensity. In field settings, simple tests are preferred. This study develops equations to estimate maximal muscle strength in upper-and lower-extremity muscles based on submaximal elastic resistance tests. Healthy adults (n = 26) performed a maximal test (1 RM) to validate the ability of the subsequent submaximal tests to determine maximal muscle strength, with elastic bands. Using a within-group repeated measures design, three submaximal tests of 40%, 60%, and 80% during (1) shoulder abduction, (2) shoulder external rotation, (3) hip adduction, and (4) prone knee flexion were performed. The association between number of repetitions and relative intensity was modeled with both 1st and 2nd order polynomials to determine the best predictive validity. For both upper-extremity tests, a strong linear association between repetitions and relative intensity was found (R2 = 0.97–1.00). By contrast, for the lower-extremity tests, the associations were fitted better with a 2nd order polynomial (R2 = 1.00). The results from the present study provide formulas for predicting maximal muscles strength based on submaximal resistance in four different muscles groups and show a muscle-group-specific association between repetitions and intensity.